INTEGRASI UNSUR HUMANISASI, LIBERASI DAN TRANSIDENSI DALAM PENDIDIKAN AGAMA ISLAM - Masbur Masbur (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2016)
Islam is a religion of tolerance for adherents and giving attitude to provide benefit to the nation in various dimension of life. Humanization is the planting of Islamic values towards the human nature through education. Humanization of education means the whole element in education that reflects the integrity of the human being and to help people become more humane. Liberalism as a doctrine of freedom is the right of every human being. Giving freedom is a recognition of human dignity, the basis concept of humanism. The values of freedom in Islam would not exist if it is not based on a deep feeling in one's personal, community needs, obedience to God and human values. Islamic education as a process of humanization require the principle of freedom to develop the potential of learners optimally. Liberalism as a doctrine of freedom is the right of every human being. Nobody is willing pressed or deprived of his rights. Therefore, every human being has the right to get freedom. Giving freedom is a recognition of human dignity, the basis concept of humanism. The values of freedom in Islam would not exist if it is not based on a deep feeling in one's personal, community needs, obedience to God and human values. Islamic education as a process of humanization require the principle of freedom to develop the potential of learners optimally. Implementation of education it is impossible to reach the goal or target if they do not give freedom. transcendental dimension of transcendence is to grow in culture. Such social sciences, then Muslims will be able to straighten out steps the development of science that's happening now and can dampen social unrest and other criminal acts that currently characterizes the lives of many. Islam contributes good activity, but in accordance with the Shari'a should implementation predetermined.